THE EFFECT OF PARTNER READING STRATEGY ON THE SECOND YEAR STUDENTS’ READING COMPREHENSION IN RECOUNT TEXT AT JUNIOR HIGH SCHOOL 40 PEKANBARU - Rahma Yeni; Indah Tri Purwanti; Marzuki Marzuki (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study was aimed at finding out the effect of Partner Reading Strategy on the second year students’ reading comprehension in recount texts at Junior High School 40 Pekanbaru. Pre-experimental research design was used for this study. The sample was selected using Cluster Random Sampling. Class VIIIE was chosen as the experimental class. The instrument for pre-test and post-test was in a form of multiple choices. The test consisted of 5 recount texts with 8 multiple choice items for each text. T-test was used to analyze the data. The results showed that there was a significant difference between students’ reading comprehension scores before and after being taught by using Partner Reading Strategy. The finding showed that the mean score of pre-test was 45.89 and the mean score of post-test was 59.55. The result also showed that the value of t-test (6.460) was higher than t-table (2.064). It means that the Alternative Hypothesis (Ha) was accepted and Null Hypothesis (Ho) was rejected. Hence, there is a significant effect of Partner Reading Strategy on the second year students’ reading comprehension in recount texts at Junior High School 40 Pekanbaru.Key Words: Effect, Partner Reading Strategy, Reading Comprehension